Who is afraid of ticks and tick-borne diseases? Results from a cross-sectional survey in Scandinavia - Slunge, Daniel; Jore, Solveig; Krogfelt, Karen Angeliki; Tugwell Jepsen, Martin; Boman, Anders (University of Gothenburg, 2019)
The dataset contains the variables used in the study "Who is afraid of ticks and tick-borne diseases? Results from a cross-sectional survey in Scandinavia", by Slunge et al 2019. The questionnaire used in the data collection contains additional questions that are not included in this material. Data is available for download in SPSS and STATA format.

Datamaterialet innehåller variablerna som använts i studien "Vem är rädd för fästingar och fästingburna sjukdomar? Resultat från en enkätundersökning i Skandinavien", av Slunge et al 2019. Frågeformuläret som används vid datainsamlingen innehåller ytterligare frågor som inte ingår i detta material. Data är tillgängliga för nedladdning i SPSS- och STATA-format.
Vem är rädd för fästingar och fästingburna sjukdomar - Resultat från en enkätundersökning i Skandinavien
Keywords: Borrelia; Borrelia; TBE; TBE; risk perception; riskuppfattning; ECONOMICS; EKONOMI; HEALTH; HÄLSA; NATURAL ENVIRONMENT; NATUR OCH MILJÖ; Medical and Health Sciences; Medicin och hälsovetenskap; Social Sciences; Samhällsvetenskap